2018
DOI: 10.1155/2018/2419686
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Whole-Genome Sequencing of TwoStreptomycesSpecies from the Rhizosphere Soil of Peony Reveal Their Characteristics as Plant Growth-Promoting Rhizobacteria

Abstract: Two bacteria, Streptomyces albireticuli MDJK11 and S. alboflavus MDJK44, which are potential plant growth-promoting rhizobacteria against pathogenic fungi were isolated from the rhizosphere soil of peony in Shandong, China. Their biological characteristics and complete genome sequences were reported in this study. The total genome size of MDJK11 was only 8.14 Mb with 6,550 protein-coding genes and a high GC content of 72.8 mol%. The MDJK44 genome comprises a 9.62 Mb chromosome with 72.1 mol% GC content, 7,285 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…were strongly correlated to both sage dry weight and mycorrhizal rates in the root biotope, which falls in line with previous studies describing Streptomyces spp. as promoting the growth of numerous plant and microbial species (Foulon et al, 2016a;Iffis et al, 2016;Dias et al, 2017;Durand et al, 2018;Vurukonda et al, 2018;Wang C. et al, 2018). It hence could be considered of great interest as both PGPB and mycorrhiza helper bacteria, depending on the species and the strain.…”
Section: Prevalence Of Pgpr In Soil and Root Bacterial Communitiesmentioning
confidence: 99%
“…were strongly correlated to both sage dry weight and mycorrhizal rates in the root biotope, which falls in line with previous studies describing Streptomyces spp. as promoting the growth of numerous plant and microbial species (Foulon et al, 2016a;Iffis et al, 2016;Dias et al, 2017;Durand et al, 2018;Vurukonda et al, 2018;Wang C. et al, 2018). It hence could be considered of great interest as both PGPB and mycorrhiza helper bacteria, depending on the species and the strain.…”
Section: Prevalence Of Pgpr In Soil and Root Bacterial Communitiesmentioning
confidence: 99%
“…Those microbes are recruited by plant exudates released through the roots [1]. In this environment, they are exposed to a permanent state of competition; the production of specific antibiotics may play a decisive role in helping them survive within the rhizosphere microbial community [2]. Among them, it has been revealed that streptomycetes could help to promote the growth of host plants as well as to improve disease symptoms caused by plant pathogens through diverse mechanisms, including the production of bioactive metabolites, which are applied in the direct antagonism against pests and diseases [3,4], in the changes of host physiological function [5], in the induction of host systemic acquired resistances [6], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, it has been revealed that streptomycetes could help to promote the growth of host plants as well as to improve disease symptoms caused by plant pathogens through diverse mechanisms, including the production of bioactive metabolites, which are applied in the direct antagonism against pests and diseases [3,4], in the changes of host physiological function [5], in the induction of host systemic acquired resistances [6], and so on. Among these characteristics, a significant common function for Streptomyces is the antibiotics production [7], which suggests that streptomycetes play a key role in the plant defense and are widely recognized for their potentials in the biocontrol [2]. For example, Blasticidin S, produced by Streptomyces griseochromogenes, was the first commercial antibiotic used in the control of rice blast in Japan [8].…”
Section: Introductionmentioning
confidence: 99%
“…VV/R4 strains reduced the fungal Streptomyces as a biocontrol agent 2 253 pathogens infection rate. Moreover, Streptomyces albi reticuli MDJK11 and MDJK44 showed robust inhibition on the F. solani growth and Streptomyces alboflavus MDJK44 showed higher biocontrol activity than S. albireticuli MDJK11 (Prapagdee et al 2008;Evangelista-Martínez 2014;Vurukonda et al 2018;Wang et al 2018;González-García, et al 2019). Several mechanisms of antagonistic phenomena against fungi, including antibiosis and parasitism, have been proposed.…”
Section: Discussionmentioning
confidence: 99%